Historical analysis of deaths from intentionally self-inflicted injuries in Paraná State according to data from DATASUS - Silva , André Inácio da (2021)
Research addressing the theme of self-inflicted violence is relevant but has been little discussed in Brazil. This study aims to analyze data on notifications of deaths from self-harm in Paraná state. This is an ecological, descriptive study with a quantitative approach based on secondary data obtained from national health information systems of notified cases of deaths from intentional self-harm in Paraná, in the period from 2009 to 2018, referring to the International Disease Code (IDC) 10 from category X60 to X84. A total of 6609 deaths from self-harm were identified with significant growth (p<0.0001) in the analyzed period, with a predominance of males (79.69%), single (49.27 %), with the highest occurrence at home (64.26%) and aged between 20 and 59 years. The main cause of death was self-inflicted injury by hanging, strangulation, and suffocation. Self-intoxication due to medications and drugs of abuse showed significant growth from 2014 onwards. In this scenario, it is concluded that epidemiological information is an important tool for understanding self-inflicted violence that can provide support for the development of prevention strategies for this problem.